ANALISA KONSOLIDASI COUPLE DARI SUATU TIMBUNAN DENGAN VERTICAL DRAINS MENGGUNAKAN PEMODELAN TANAH SOFT SOIL (CAP) STUDI KASUS : PROYEK PEMBANGUNAN JALAN LINGKAR UTARA SEMARANG FASE - II - Hardiyanto (NIM 25098054), Irwan
Abstract : Soil Improvement using preloading and vertical drain is relatively more effective compared to other soil improvement method. Easy to construct, and relatively more economical in cost, is the major advantages of this method. The purpose of preloading is to accelerate consolidation process of weak and soft soil layer as bearing stratum, and to gain soil shear strength prior to impose of the actual final load. Therefore the stages of loading can be planned so the soil finally will be able to carry design load and the excessive settlement can be reduced. This thesis will explain and present a methodology regarding 2-dimensional (plane strain) modeling of vertical drain, by considering the effect of 3-dimensional (axisymmetry) of consolidation and smear zone. Analysis will be conducted using finite element program. Theory of consolidation from Biot will also be explained in brief in connection with 3-D consolidation. The main objective of the study is on the application how to model and to analyze an embankment and vertical drains in correlation with soft clay behavior, by using finite element computer program. Eventhough the actual condition on site is axisymmetry, an equivalent model of plane strain will adequately practical to be applied in designing the preloading stages and vertical drains system. Case study is taken on a \"Designing the consolidation process with preloading and vertical drains for Semarang Northern Ring Road Phase 11 Project\". Analysis had been conducted with taking into account the conversion of axisymmetry influence of PVD (prefabricated vertical drain) to Plane Strain parameters. The analysis result has also been compared with monitoring data from the site (settlement plate and piezometer). The comparison shows a quite reliable result.p